New perspectives for fascioliasis in Upper Egypt's new endemic region: Sociodemographic characteristics and phylogenetic analysis of Fasciola in humans, animals, and lymnaeid vectors - Alzahraa Abdelraouf Ahmad; Haidi Karam-Allah Ramadan; Waleed Attia Hassan; Mohammed Ageeli Hakami; Enas Abdelhameed Mahmoud Huseein; Sara Abdel-Aal Mohamed; Adnan Ahmed Mohamed; Nahed Ahmed Elossily (Public Library of Science (PLoS), 2022)
Background Fascioliasis is a significant vector-borne disease that has emerged in numerous tropical and subtropical countries causing severe health problems. Egypt is one of the fascioliasis endemic regions; however, the current situation in Upper Egypt is understudied, with only sporadic human cases or outbreaks. This study aims to highlight the sociodemographic characteristics of human fascioliasis in a newly emerged endemic area in Upper Egypt, along with risk factors analysis and the molecular characteristics of the fasciolid population in humans, animals, and lymnaeid snails. Methodology/Principal findings The study reported Fasciola infection in patients and their close relatives by analyzing the risk of human infection. Morphological and molecular characterization was performed on lymnaeid snails. Multigene sequencing was also used to characterize fasciolids from human cases, cattle, and pooled snail samples. The study identified asymptomatic Fasciola infection among family members and identified the presence of peridomestic animals as a significant risk factor for infection. This is the first genetic evidence that Radix auricularia exists as the snail intermediate host in Egypt. Conclusions/Significance This study revealed that Assiut Governorate in Upper Egypt is a high-risk area for human fascioliasis that requires additional control measures. Fasciola hepatica was the main causative agent infecting humans and snail vectors in this newly emerged endemic area. In addition, this is the first report of R. auricularia as the snail intermediate host transmitting fascioliasis in Upper Egypt. Further research is required to clarify the widespread distribution of Fasciola in Egypt's various animal hosts. This provides insight into the mode of transmission, epidemiological criteria, and genetic diversity of fasciolid populations in Upper Egypt.\ Author summary Human fascioliasis is a freshwater snail-transmitted disease that is widely distributed in many tropical and subtropical countries including Egypt. Recently, Upper Egypt reported sporadic cases of human fascioliasis and a few outbreaks establishing a new endemic area. This study was conducted to get information on the sociodemographic characteristics of the infected patients and possible risk factors of infection in this recently emerged endemic region. Further, this study tried to describe lymnaeid intermediate host snails involved in infection transmission morphologically and by molecular analysis. Analysis of the phylogenetic relationships between natural fasciolid populations was performed in humans, animals, and snail isolates by multilocus sequencing. Results indicated that asymptomatic fascioliasis should be screened in areas at risk of infection. Also, younger age groups and the presence of peri domestic animals were significantly associated with an increased risk of infection. This is the first molecular proof of the existence of Radix auricularia snails causing fascioliasis in Egypt. Results showed that Upper Egypt may be an area at risk for human fascioliasis that needs additional control measures.